Diálogos com Paradox: o percurso de um vídeo didático, de sua concepção à sua experiência por professores de inglês - Machado, Paulo Eduardo Ferreira (2007)
This study aims to interpret the process of creation, by the researcher himself, of a didactic video named Paradox. It also intends to interpret and reinterpret the material under a contemporary perspective, backed, on one side, by theoretical frameworks and by the search of understanding the dialogue of English Teachers with a didactic video, taken as a phenomenon of human lived experience. The investigation relies on the support of a panel of theories of learning (Giusta 2003; Williams and Burden, 1997), with a greater focus on the sociointeractionism (Vygotsky, 1938/2003) and on the concept of post-method (Kumaravadivelu, 2001). Language, in this study, is understood as a dialogic social practice (Bakhtin and his circle, 1979/1997, 1926/2000, 1929/2004) with contributions about audiovisual language (Babin and Kouloumdjian, 1989), and also about didactic video (Ferrès, 1996). In methodological terms, the option was the hermeneuticalphenomenological approach (Ricoeur, 2001; van Manen, 1990) which interprets phenomenons of lived experiences by the means of writings generated by those experiences. The interpretive quest, in this research, follows the path of a retrospective narration of the designer, inserting the video Paradox within the historic and professional contexts of its creation; it observes the video with a contemporary view from the vantage point of the bakhtinian theory; finally, it lies on dialogues with nine English teachers from diverse professional contexts, about their experiences with Paradox, in the sense of interpreting the phenomenon of the dialogue of English teachers with a didactic video. The retrospective narration and the interpretation of the video by the participants reveal an audio-verb-visual enunciation, interpreted in its intertextual relations as a result of an axiological posture of an author-creator. The achieved results from the dialogues with the participants show that the phenomenon under scrutiny is structured by the themes: reflection, application and questioning